Application of STEM in Educational Curricula: a Literature Review - Jumri, Rahmat (Aksioma Education Journal, 2025)
This study aims to examine the implementation of the Science, Technology, Engineering, and Mathematics (STEM) approach in educational curricula through a systematic literature review (SLR) method using the PRISMA framework. The main focus of this research is to evaluate how the STEM approach is integrated into various educational levels, identify implementation challenges, and assess its impact on the development of 21st-century skills such as critical thinking, creativity, communication, and collaboration (4C). Data were obtained from 239 scholarly articles accessed through databases such as Google Scholar, Scopus, SINTA, GARUDA, Crossref, and ICI. After a rigorous selection process based on inclusion criteria, 25 articles were chosen for further analysis. The results of the study indicate that consistent STEM implementation can enhance student motivation, interdisciplinary concept understanding, and problem-solving skills. However, several barriers were also identified, such as a lack of teacher training, limited resources, and low educational policy support. Therefore, this study provides valuable contributions to formulating recommendations for the development of more effective STEM-based educational policies in the future.